Bank holding company dividends and repurchases during the financial crisis - Beverly Hirtle (Federal Reserve Bank of New York, 2014)
Many large U.S. bank holding companies (BHCs) continued to pay dividends during the recent financial crisis, even as financial market conditions deteriorated, large losses accumulated, and emergency capital and liquidity were being provided by the official sector. In contrast, share repurchases by these BHCs dropped sharply in the early part of the crisis. Documenting this divergent behavior is one of the key contributions of this paper, as previous analysis has tended to focus on dividend payments alone. The paper also examines the role that repurchases played in large BHCs' decisions to reduce or eliminate dividends. Did BHCs with a high level of repurchases prior to the financial crisis cut dividends later, or by less, than BHCs with lower levels of pre-crisis repurchases? The key findings are that the smaller BHCs in the sample (those with assets between 5 billion and 25 billion) with higher levels of repurchases before the financial crisis reduced dividends later and by less than BHCs with lower pre-crisis repurchases. In contrast, larger BHCs with higher pre-crisis repurchases tended to reduce their dividends earlier in the financial crisis, though there is no relationship between pre-crisis repurchases and the size of dividend reductions for these institutions.
Keywords: G01; G21; G28; G35; 330; bank capital; stock repurchases; bank dividends; financial crisis